2022
DOI: 10.1063/5.0085412
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and hydrodynamics of spontaneous and forced imbibition in conical capillaries: A theoretical study of conical liquid diode

Abstract: Thermodynamics and hydrodynamics of spontaneous and forced imbibition of liquid into conical capillaries are studied to assess the feasibility of a conical liquid diode. The analytical formulas for the Laplace pressure and the critical Young's contact angle of the capillary for the onset of spontaneous imbibition are derived using the classical capillary model of thermodynamics. The critical contact angle below which the spontaneous imbibition can occur belongs to the hydrophilic region for the capillary with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…In addition to hydrodynamic cloaking metamaterials, numerous other hydrodynamic metamaterials are not intended for cloaking purposes, such as liquid diodes, [64,65,[65][66][67][68][69] liquid gates, [70][71][72] among other aspects. Since these studies have already been reviewed in the relevant literature, we will not expand too much on them.…”
Section: Hydrodynamic Metamaterials Beyond Cloakingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to hydrodynamic cloaking metamaterials, numerous other hydrodynamic metamaterials are not intended for cloaking purposes, such as liquid diodes, [64,65,[65][66][67][68][69] liquid gates, [70][71][72] among other aspects. Since these studies have already been reviewed in the relevant literature, we will not expand too much on them.…”
Section: Hydrodynamic Metamaterials Beyond Cloakingmentioning
confidence: 99%
“…[53][54][55][56][57][58][59][60][61][62][63] Hence, numerous researchers have investigated bionic liquid diodes. [64][65][66][67][68][69] Similar to an electronic diode that can conduct current in the forward direction and block it in the reverse direction, a liquid device that can rectify liquids to flow in a directional manner can be treated as a "liquid diode". It is noteworthy that although traditional mechanical valves can also perform unidirectional transport functions, traditional mechanical valves are relatively bulky compared to liquid diodes.…”
Section: Liquid Diodesmentioning
confidence: 99%
“…Gorce et al explored the optimal imbibition of liquids with different curvature tubes. Singh et al and Iwamatsu presented theoretical investigations of liquid imbibition into capillaries with axially varying geometry, and they found that the conical capillary tube can act as a liquid diode. Michielsen et al have done extensive theoretical work on droplet motion on the outer surface of conical tubes from an energetic point of view, and their work also takes into account the effects of the droplet volume, contact angle, and angle of change of the tube on droplet self-transport.…”
Section: Introductionmentioning
confidence: 99%